Influence of allowance, lifestyle, and financial inclusion on financial management practice among Indonesia college students - Zaniarti, Sri; Margaretha, Meily; Subagja, Arie Danu (Goodwood Publishing, 2025)
Purpose: This study investigates how young adults manage their finances. It examines the impact of three factors: allowance (pocket money), financial habits (lifestyle), and access to financial services (inclusion). Methods: The study population comprised college students in Bandung, Indonesia. A sample of 159 college students was selected to understand their financial management practices and related factors. Results: The study found that Allowance and financial inclusion significantly influenced how young adults managed their finances. These factors were found to have a significant impact, with p-values less than 0.05. Students who manage their income exhibit better budgeting and spending habits. Access to financial services positively affects students' financial management skills and encourages safer savings methods. However, lifestyle factors did not significantly impact financial management, contrary to the findings of previous research. This suggests that other factors might be more crucial for financial discipline. Conclusions: This study finds that pocket money and financial inclusion significantly enhance financial management skills among university students, while lifestyle has little impact, highlighting the need for education that fosters saving, investing, and responsible financial behavior. Limitations: This study focused on a specific student population in Bandung, Indonesia. Further research is required to determine whether these findings apply to broader demographic groups. Contribution: This study underscores the role of schools and families in enhancing students’ financial literacy through education, allowances, and financial inclusion. Novelty: This study reveals that lifestyle habits have a limited impact on financial management among tech-savvy youth, suggesting the need to reconsider financial education strategies, particularly in trend-driven contexts such as Bandung.